Respuesta :
This is system of Equations.
2x + 3y =10
x + y = 3
x + y = 3 (multiply this by three) to get 3x + 3y = 9
2x + 3y =10
3x + 3y = 9 Subtract them
-1x = 1
x=-1
Now plug x back into the top equation and solve for y.
I hope this helps! If not, let me know! Have a fantastical day!
2x + 3y =10
x + y = 3
x + y = 3 (multiply this by three) to get 3x + 3y = 9
2x + 3y =10
3x + 3y = 9 Subtract them
-1x = 1
x=-1
Now plug x back into the top equation and solve for y.
I hope this helps! If not, let me know! Have a fantastical day!